Efficiency of perturbation‐selection and its orbital dependence in the SAC‐CI calculations for valence excitations of medium‐size molecules. Issue 30 (15th September 2014) - Fukuda, Ryoichi; Ehara, Masahiro
<x xml:space="preserve">Abstract</x> The efficiency and accuracy of the perturbation‐selection used in the symmetry‐adapted cluster‐configuration interaction (SAC‐CI) calculations are investigated for several low‐lying valence excited states of 21 medium‐size molecules, including typical chromophores with heterocyclic macrocycles (free‐base porphine, coumarin, indole, and BODIPY), nucleobases, amino acids (tyrosine and tryptophan), polycyclic aromatic hydrocarbons, and organometallics (ferrocene and Re(bpy) <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m478m70" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(CO)4+1</alternatives>). Benchmark SAC‐CI calculations with up to 110 million operators are performed. The efficiency of the perturbation‐selection depends on the molecular orbitals (MOs); therefore, the canonical MO and localized MO (LMO) obtained by Pipek‐Mezey's method are examined. Except for the highly symmetric molecules, using LMOs improves the efficiency and accuracy of the perturbation‐selection. With using LMOs and perturbation‐selection, sufficiently reliable results can be obtained in less than 10% of the computational costs required for the full‐dimensional calculations. The perturbation‐selection with LMOs is suggested to be a promising method for excited states in larger molecular systems. Copyright © 2014 Wiley Periodicals, Inc.